Push a novel - Sapphire 1950- (New York Vintage Contemporaries/Vintage Books, 1997)
Relentless, remorseless, and inspirational, this "horrific, hope-filled story" ("Newsday") is certain to haunt a generation of readers. Precious Jones, 16 years old and pregnant by her father with her second child, meets a determined and highly radical teacher who takes her on a journey of transformation and redemption.
Keywords: Child abuse -- Fiction; Incest -- Fiction; Teenage mothers -- Fiction; Literacy -- Fiction; African American girls -- Fiction; African Americans -- New York (State) -- New York -- Fiction; Harlem (New York, N.Y.) -- Fiction